2008
DOI: 10.1016/j.brainres.2008.02.093
|View full text |Cite
|
Sign up to set email alerts
|

Glia maturation factor modulates β-amyloid-induced glial activation, inflammatory cytokine/chemokine production and neuronal damage

Abstract: Glia maturation factor (GMF), discovered and characterized in our laboratory, is a highly conserved protein primarily localized in mammalian central nervous system. Previously we demonstrated that GMF is required in the induced production of proinflammatory cytokines and chemokines in brain cells. We now report that ventricular infusion of human amyloid beta peptide1-42 (Abeta1-42) in mouse brain caused glial activation and large increases in the levels of GMF as well as induction of inflammatory cytokine/chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 42 publications
3
66
0
Order By: Relevance
“…Several in vitro studies have demonstrated that Ab might function as an immune stimulus for microglia or astrocyte activation and lead to neuroinflammation in the brain of AD patients or animals (Meda et al 1995;MiguelHidalgo et al 2002;Zaheer et al 2008). Consistently, the present study showed that unilateral hippocampal injection of Ab resulted in obvious inflammatory responses, manifested as the significant increase in markers of astrocytic and microglial activation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Several in vitro studies have demonstrated that Ab might function as an immune stimulus for microglia or astrocyte activation and lead to neuroinflammation in the brain of AD patients or animals (Meda et al 1995;MiguelHidalgo et al 2002;Zaheer et al 2008). Consistently, the present study showed that unilateral hippocampal injection of Ab resulted in obvious inflammatory responses, manifested as the significant increase in markers of astrocytic and microglial activation.…”
Section: Discussionsupporting
confidence: 84%
“…Abinduced neurotoxicity, which leads to the selective cholinergic neuronal apoptosis, involves multiple mechanisms. Besides direct neuronal damage, excitotoxicity and oxidative stress, Ab can function as an immune stimulus for glial activation and evoke chronic neuroinflammation in brain of AD patients or animals (Meda et al 1995;Miguel-Hidalgo et al 2002;Zaheer et al 2008). Therefore, enhancement of acetylcholine (ACh) concentration by inhibiting acetylcholinesterase (AChE) activity or blockade of the neuroinflammation by inhibiting the action of proinflammatory mediators has been regarded as important strategies for AD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…receptor for advanced glycosylation endproducts (RAGE), NOD-, LRR-and pyrin domain-containing 3 (NLRP3)), microglia are activated, leading to the production of cytokines (e.g. interleukin (IL)-1b, IL-6, IL-8, tumor necrosis factor-a (TNF-a), chemokines, and nitrogen species, which damage neurons; Zaheer et al, 2008). This proinflammatory response is sustained over time and can cause neuronal death, which in turn, overactivates microglia, in a cycle termed reactive microgliosis.…”
Section: The Role Of Microglia In Alzheimer's and Parkinson's Diseasesmentioning
confidence: 99%
“…Microglia activated in vitro induce the expression of proinflammatory cytokines, including IL-6, IL-8, TNF-a, reactive oxygen/nitrogen species, and chemokines, all of which are known to cause neuronal damage (Van Eldik et al, 2007;Zaheer et al, 2008;Fernández et al, 2013). Studies on brain tissue derived from patients with AD have shown that CB2 modulates hippocampal function in the context of AD pathology (Benito et al, 2003).…”
Section: Discussionmentioning
confidence: 99%